Repurposing Antimalarial Pyronaridine as a DNA Repair Inhibitor to Exploit the Full Potential of Gold-Nanoparticle-Mediated Radiation Response - Nolan Jackson; Abdulaziz Alhussan; Kyle Bromma; David Jay; James C. Donnelly; Frederick G. West; Afsaneh Lavasanifar; Michael Weinfeld; Wayne Beckham; Devika B. Chithrani (MDPI AG, 2022)
Radiation therapy (RT) is frequently used to locally treat tumors. One of the major issues in RT is normal tissue toxicity; thus, it is necessary to limit dose escalation for enhanced local control in patients that have locally advanced tumors. Integrating radiosensitizing agents such as gold nanoparticles (GNPs) into RT has been shown to greatly increase the cure rate of solid tumors. The objective of this study was to explore the repurposing of an antimalarial drug, pyronaridine (PYD), as a DNA repair inhibitor to further enhance RT/GNP-induced DNA damage in cancerous cell lines. We were able to achieve inhibitory effects of DNA repair due to PYD at 500 nM concentration. Our results show a significant enhancement in DNA double-strand breaks of 42% in HeLa cells treated with PYD/GNP/RT in comparison to GNP/RT alone when irradiated with a dose of 2 Gy. Furthermore, there was a significant reduction in cellular proliferation for both HeLa and HCT-116 irradiated cells with the combined treatment of PYD/GNP/RT. Therefore, the emergence of promising novel concepts introduced in this study could lay the foundation for the transition of this treatment modality into clinical environments.